Anomalous thickness dependence of Curie temperature in air-stable two-dimensional ferromagnetic 1T-CrTe2 grown by chemical vapor deposition - Meng, Lingjia; Zhou, Zhang; Xu, Mingquan; Yang, Shiqi; Si, Kunpeng; Liu, Lixuan; Wang, Xingguo; Jiang, Huaning; Li, Bixuan; Qin, Peixin; Zhang, Peng; Wang, Jinliang; et al. (Nature communications, 2021)
The discovery of ferromagnetic two-dimensional van der Waals materials has opened up opportunities to explore intriguing physics and to develop innovative spintronic devices. However, controllable synthesis of these 2D ferromagnets and enhancing their stability under ambient conditions remain challenging. Here, we report chemical vapor deposition growth of air-stable 2D metallic 1T-CrTe 2 ultrathin crystals with controlled thickness. Their long-range ferromagnetic ordering is confirmed by a robust anomalous Hall effect, which has seldom been observed in other layered 2D materials grown by chemical vapor deposition. With reducing the thickness of 1T-CrTe 2 from tens of nanometers to several nanometers, the easy axis changes from in-plane to out-of-plane. Monotonic increase of Curie temperature with the thickness decreasing from ~130.0 to ~7.6 nm is observed. Theoretical calculations indicate that the weakening of the Coulomb screening in the two-dimensional limit plays a crucial role in the change of magnetic properties. Here, the authors report chemical vapor deposition growth of metallic 1T-CrTe 2 ultrathin crystals with controlled thickness and long-range ferromagnetic ordering, and observe a monotonic increase of the Curie temperature with decreasing thickness.